Pengembangan Metode Evaluasi Pembelajaran Berbasis Quizizz Berbantuan E-Modul dalam Menunjang Kegiatan Pembelajaran di Kelas X APAPL SMKN 9 Makassar - Afiifah, Azzah; Sukainah, Andi; Rahman, Khaidir (Agricultural Technology Education Study Program, 2024)
In the learning process, the success or failure of the delivery of material carried out is measured in giving tests or evaluations. Evaluation is one of the important aspects of the learning process. One of the evaluation media that can be used is quizizz. This study aims to develop and analyze the results of validation and student responses to the use of evaluation media. The media developed is a quizizz-based evaluation tool with the help of e-modules. This research uses a research and development (R&D) approach with the ADDIE development model. The subjects of the study were 23 class X students majoring in Brackish Water and Sea Fisheries Agribusiness (APAPL) SMKN 9 Makassar, media experts, and material experts. The results showed: (1) The validation assessment of media experts obtained an average value of 3.69 and 3.87. (2) The material expert validation assessment obtained an average score of 4.0 and 4.0. Based on the average validation scores of the two experts, it can be said that the evaluation tool is declared feasible to use because it is in the very valid category. (3) The average result response of 12 small group students amounted to 81.83 who were in the very good category. (4) The average result response of 23 large group students amounted to 84.56 who were in the very good category. Based on the average scores of the two group trials, it can be stated that the development of evaluation tools is declared feasible for use and is in the very good category to be applied.